Integrating Internet of Things Technology to Enhance Highland Vegetable Productivity : A Systemic Review with Empirical Evidence from Aceh Tengah, Indonesia - Ihsan, Muhammad; Susanto, Herdi; Joli Supardi; Nuzuli Fitriadi (Jurnal Inotera, 2026)
Global food security challenges necessitate transformative approaches to enhance agricultural productivity, particularly in highland regions facing multiple production constraints. This systematic literature review examines the potential of Internet of Things (IoT) technology integration to enhance productivity of highland vegetables (potato, cabbage, and carrot) in Aceh Tengah District, Indonesia. A critical agricultural region at 1,000-2,600 m.a.s.l. Following PRISMA guidelines, we analyzed peer-reviewed publications (2020-2025) on IoT applications in vegetable production, synthesizing evidence from successful implementations across diverse geographical contexts. Empirical evidence demonstrates that precision agriculture systems incorporating soil moisture sensors, nutrient monitoring, weather stations, and disease detection algorithms achieve productivity increases of 10-20% while reducing water consumption by 20-30% and input costs by 13%. However, IoT adoption in Indonesian highland agriculture remains below 5%, constrained by infrastructure limitations, digital literacy gaps, and economic barriers. This review identifies six critical research gaps and proposes a contextualized framework for IoT implementation adapted to smallholder farming systems in highland Indonesia. The framework addresses technological, socioeconomic, and institutional dimensions essential for sustainable digital transformation of highland agriculture. A pilot project framework is proposed targeting productivity enhancement, resource efficiency, and capacity building for sustainable implementation in Aceh Tengah's unique agroecological context